President's Annual Report, 1982-1983 - Bailey, Hugh C. (Valdosta State University Archives and Special Collections, 1983)
The Valdosta State College President's Annual Report for fiscal year 1982-1983 by Hugh C. Bailey.
Keywords: Valdosta State University; College publications; Corporate reports; College presidents